Factors associated with the psychological status during the Coronavirus pandemic, baseline data from an Iranian Province - Mohammad Mostafa Ansari Ramandi; Hossein Yarmohammadi; Somayeh Beikmohammadi; Behzad Hassan Hosseiny Fahimi; Alireza Amirabadizadeh (Babol University of Medical Sciences, 2020)
Background: The 2019 coronavirus disease (COVID-19) is threatening public health in many ways. The psychological situation of individuals is important and limited data is available from Iran. In this study, we aimed to illustrate the psychological distress of the general population and evaluate factors affecting it.  Methods: An online cross-sectional survey was done from 29th to 31st March 2020 in South Khorasan province, affected later than other parts of the country. We included sociodemographic questions, Hospital Anxiety, and Depression Scale (HADS) questionnaire and questions addressing various symptoms and diseases. Most questions had multiple choices to be chosen from and some were open questions. Univariate and multivariate analysis in SPSS software were used to find significant relationships. Results: A total of 844 responses were collected, from which 788 records were included in the analysis. The mean age of responders was 36.61 ± 10.97 (age range: 18-88) and 484 (61.4%) of them were female. The mean scores in the anxiety and depression subscale of the HADS questionnaire were 7.01±3.68 and 6.72±3.71 respectively. Experiencing cardiovascular and COVID-19 related symptoms was significantly associated with a higher number of individuals having abnormal anxiety and depression results (p value<0.001). Widowed individuals, females and those experiencing above-stated symptoms showed a significant association with increased anxiety and depression in multivariate analysis. Conclusions: Although many existing elements influence the psychological well-being of society during a pandemic, experiencing symptoms related to other diseases or having multiple chronic diseases may cause an extra burden on the psychological state of the society.